Ukrainian Experience of State Regulation of Stock Exchange Activity - Reznik N.; Abuselidze G.; Ostapchuk A.; Tkachuk V. (SHS Web of Conferences, 2019)
Theme of stock market is on the level of development in some countries. It faces a number of problems for the first time and there are no mechanisms for its overcoming. There are offers how to overcome the most popular problems of countries where the stock market just start to develop. The main part is belonging to state intervention and formation of legislative bases. Due to methods of analysis and generalization the article offers measures and mechanism of action for countries which have the same problems like Ukrainian. This research can be applied as it is or become the basis for development of new recommendations for the regulation of stock market activity.